Droplet and Percolation Network Interactions in a Fuel Cell Gas Diffusion Layer. Issue 8 (1st May 2020) - Mularczyk, Adrian; Lin, Qingyang; Blunt, Martin J.; Lamibrac, Adrien; Marone, Federica; Schmidt, Thomas J.; Büchi, Felix N.; Eller, Jens
Abstract : Product water accumulations in polymer electrolyte fuel cells can cause performance losses and reactant starvation leading to cell degradation. Liquid water removal in the form of droplets, fed by percolation networks in the gas diffusion layer (GDL), is one of the main transport mechanisms by which the water is evacuated from the GDL. In this study, the effect of droplet detachment in the gas channel on the water cluster inside the GDL has been investigated using X-ray tomographic microscopy and X-ray radiography. The droplet growth is captured in varying stages over a sequence of consecutive droplet releases, during which an inflation and deflation of the gas-liquid interface menisci of the percolating water structure in the GDL has been observed and correlated to changes in pressure fluctuations in the water phase via gas-liquid curvature analysis.